Design and analysis of bandwidth efficient WDM channel allocation for four-wave mixing effect minimization - Thing, Vrizlynn Ling Ling. (2008)
This project aims to study the factors affecting the performance of WDM systems. It then focus on the most serious degrading nonlinear factor, which is FWM. Existing methods to reduce FWM effect through channel allocation will be studied and analyzed. An efficient method will then be designed to reduce the FWM effect so as to improve WDM system performances.